Doctorate Holders: Labour Market and Mobility Indicators - Laudeline Auriol; Max Misu; Rebecca Freeman (Foresight and STI Governance)
Having benefitted from highly specialised research training, doctoral holders stand in a position to drive forward advances in science, technology and knowledge about society. Unfortunately, evidence on their careers is limited and sparse, owing, for example, to the fact that standard statistical sources are typically far too small to produce statistically robust results for this population. With a view to better understanding the labour market, career path and mobility of doctorate holders, the OECD, in coordination with the UNESCO Institute for Statistics and Eurostat, launched in 2004 a specific project on the Careers of Doctorate Holders (CDH). This paper provides an overview of the key statistical and analytical findings that draw on data from the second international CDH data collection conducted in 2010. It analyses the labour market and employment patterns of doctorate holders. Then, it looks at some important specificities of the doctoral job market, such as employment in research and patterns of job-to-job and international mobility.